Genesis Pedon Tanah yang Berkembang di Atas Batuan Karbonat Wonosari Gunungkidul - Djoko Mulyanto; S Subroto P.S.; Herwin Lukito (Universitas Muhammadiyah Surakarta, 2011)
The variation of soil color that developed on carbonate rocks which are generally white, very interesting to be studied. The aim of the study is to examine the formation of two pedons of black soil and red soil by hue 10 YR and hue 5 to 2.5 YR which successively developed on marly limestones and calcarenite. Analysis of mineral properties consist of the total minerals of sand fraction, clay fraction and rock powders. Soil chemical properties include: pH, organic C, exchangeable cations and cation exchange capacity, CaCO3, the amorphous-crystalline of Fe and Mn, the total of Fe and Mn, the analysis of physical properties is the texture of seven fractions. The results showed that the development of the red soil is much more developed than black soil that shown by intensively decalcification process of red soil that impact on the low of pH, base saturation and cation exchange capacity, whereas the development of black soil is inhibited. The formation of black soil is more inherited of clay bearing marly limestone after carbonate dissolution, whereas the red soil development through rubification and illuviation.